EDMODO AS EDUCATIONAL SOCIAL NETWORK IN TEACHING COURSE DESIGN OF EYL - Nina Puspitaloka; Indah Rahmawati; Derinda Octaviyenty Sonjaya (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This research is conducted to find out Edmodo can increase student’s ability in learning course design of EYL and student’s perception in learning course design of EYL by using Edmodo. A mixed method was used to collect quantitative and qualitative data. In answering those two research questions, the researcher used test (pre-test and post-test) to collect quantitative data and also used interview as data gathering technique to collect qualitative data. The findings of the research showed that: (1) Edmodo can increase student’s ability in learning course design of EYL. It is proven by the score of Independent T-test -0,741 and sig (2 tailed) was higher than degree of significance (0,462 < 0,05). (2) Student’s perception in learning course design of EYL by using Edmodo showed that Edmodo in learning course design of EYL can help students more understand the materials because they can get more information about materials of EYL especially course design of EYL; they can discuss the materials each other anywhere and anytime; they felt more interesting and happy; they are more confident to express their ideas, therefore they can be more active in learning course design of EYL.